Performance evaluation of mechanical blossom thinning in trunk type pear orchard - Lei, Xiaohui; Lyu, Xiaolan; Zhang, Meina; Lu, Daipeng; Wang, Shilin; Chang, Youhong; Zhong, Dexin; Shen, Tianbing (International Journal of Agricultural and Biological Engineering, 2021)
In order to yield a marketable product, hand fruit thinning (HFT) has become the major but costly management practice in modern pear planting. Two kinds of new blossom thinners for pear blossom thinning were developed, which are tractor-mounted three arms blossom thinner (TTBT) and hand-held electric blossom thinner (HEBT). Four treatments for 24 trunk type ‘Cuiguan’ pear trees (7 years) were tested. They are TTBT combined with HFT, HEBT combined with HFT, hand blossom thinning (HBT) combined with HFT, and HFT only. Pear trees were divided into 4 groups equally. Four indexes were used to evaluate the test: flower reserve rate, fruit set rate, work efficiency and cost, fruit yield, and quality. Pear canopy was divided into the inner, middle, and outer 3 layers in the top view. 20 inflorescence samples were selected for each layer. Field tests showed: there was no obvious difference in quality between mechanical blossom thinning and HBT, and the working stability of TTBT was higher than other treatments. Mechanical blossom thinning decreased the fruit set rate to a certain degree, but did not reduce the yield and quality of harvesting. TTBT could save 61.35% operation time compared with HFT, and the profitable area was 5845.76 m2. TTBT is suitable for large-scale sparse layer trunk-type pear orchards. HEBT could save 36.01% operation time compared with HFT, and the profitable area was 663.96 m2. HEBT is suitable for small and medium-sized trunk-type pear orchards. Blossom thinning can improve the average weight of high quality fruit and brix of sugar solids.Keywords: mechanical blossom thinning, pear orchard, trunk type, performance evaluationDOI: 10.25165/j.ijabe.20211404.6060Citation: Lei X H, Lyu X L, Zhang M N, Lu D P, Wang S L, Chang Y H, et al. Performance evaluation of mechanical blossom thinning in trunk type pear orchard. Int J Agric & Biol Eng, 2021; 14(4): 106–112.